Special Considerations for Proprietary Name Review: Focus on Products That May Be Prescribed "As Directed". (May 2019) - Rider, Briana B.; Mehta, Hina; Merchant, Lubna
Background: Look-alike and sound-alike (LASA) drug name similarity is often cited as a major factor contributing to wrong drug errors. When present on a prescription, differing product characteristics or directions for use may help health care professionals differentiate between 2 LASA drug names. However, evidence suggests that 1% to 5% of prescriptions include only the signa "use as directed" rather than explicit directions for use. Methods: Using nationally projected US outpatient physician survey data, we analyzed drug classes and their associated signa to identify products commonly prescribed with the signa "as directed." Results: The following categories of products are commonly associated with the signa "as directed": (1) inhalers; (2) oral contraceptives; (3) one-time treatments, such as those for lice or scabies; (4) prepackaged items with specific directions for use on the package; (5) migraine medications; (6) erectile dysfunction medications; (7) bowel evacuation/colonoscopy preparations; (8) topical medications; (9) medications with regimens that may change frequently (eg, warfarin, insulin); (10) otic products; (11) transdermal products; (12) products administered vaginally; (13) products administered rectally; and (14) products that may be titrated upon initiation. Conclusions: Prescriptions for these products with the signa "as directed" may not include product characteristics or other directions for use. The potential for products to be prescribed with the signa "as directed" should be taken into consideration when evaluating the safety of proposed proprietary names. Sponsors and the FDA can use the results of our research to aid in the selection and review of proposed proprietary names, respectively.